Urinary nitrogen compounds in dairy cows fed urea as the sole or partial source of nitrogen - Ettala, Terttu; Kreula, Matti (Agricultural and Food Science, 1976)
Urinary nitrogen compounds were determined in test cows with urea as the sole (0-cows) or partial (ULP-cows) source of nitrogen. An average of 0.49 % total nitrogen was found in 0-cows and 0.88 % in ULP-cows, the values for urea nitrogen being 2.24 and 2.63 mg/ml, for ammonium nitrogen 0.14 and 0.09 mg/ml, for creatinine 0.77 and 0.90 mg/ml and for creatine 0.28 and 0,42 mg/ml urine, respectively. Differences between the two groups were highly significant (P < 0.001) as regards total nitrogen and significant (P < 0.05) as regards urea nitrogen and creatine. In each group the between-cow differences were highly significant with regard to total and urea nitrogen and creatine, and in 0-cows also with regard to ammonium nitrogen and creatinine. Smaller amounts of urinary allantoin and larger amounts of uric acid were found in 0-cows than in ULP-cows. Corresponding determinations were made to some extent also on the urine of cows on normal indoor or pasture feeding.